Miguel de Cervantes - Goldberg, Jake. (Philadelphia : Chelsea House, 1993)
Describes the life and career of the noted Spanish writer, including the creation of his masterpiece "Don Quixote.".
Includes bibliographical references (p. 107-108) and index.
Wilson's Junior High School.
7.9
5-8
7-9
Keywords: Cervantes Saavedra, Miguel de, -- 1547-1616 -- Juvenile literature; Cervantes Saavedra, Miguel de, -- 1547-1616.; Cervantes Saavedra, Miguel de, -- 1547-1616.; Authors, Spanish -- Classical period, 1500-1700 -- Biography -- Juvenile literature; Authors, Spanish; Spanish authors -- Biography